An accelerometer based sensor platform for insitu elite athlete performance analysis - James, D. A.; Davey, N.; Rice, T. (Proceedings of the IEEE, Sensors, 2004, 2004)
A sensor data acquisition platform has been developed for in-situ sporting applications encompassing stand alone high speed sampling and storage of multiple accelerometer data. Ambulatory monitoring of elite athletes in competition or training environments was then undertaken. The platform itself is divided into functional blocks and controlled by a small microcontroller using a custom OS. Hence it is easily customizable for a variety of sporting applications. The platform is packaged so as to be robust, hermetically sealed and biomechanically neutral to the athlete. Results and derivative data from rowing and swimming are presented as sample applications. In swimming applications, stroke characteristics for a variety of training strokes are analyzed and found to be better than other methods. The rowing application, when coupled with other monitoring techniques such as impeller velocity, enables recovery of intra and inter stroke phases as a means to assess performance over the entire course and has been used by competition rowers to improve performance at national and international competitions.